3sqrt(3) - sqrt(45) + 3sqrt(13)= 3sqrt(3) - 3sqrt(5) + 3sqrt(13) = 3*[sqrt(3) - sqrt(5) + sqrt(13)] where the expression in parenthesis cannot be simplified.
The value is 9.3046, approx.
Chat with our AI personalities
True
Same mathematical signs equal plus Different mathematical signs equal minus Plus Plus = Plus (+)(+) = + Minus Minus = Plus (-)(-) = + Plus Minus = Minus (+)(-) = - Minus Plus = Minus (-)(+) = - So the direct answer to your question would be: plus minus equals minus
zero
13+13+13+13+13+13+13+13+13+13 = 13 * 10 = 130.
6w